1984
DOI: 10.1677/joe.0.1010289
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone increases the number of ova shed in the cyclic hamster and guinea-pig

Abstract: Osmotic minipumps containing 400 micrograms ovine LH installed subcutaneously on day 1 (oestrus) of the cycle in the hamster induced superovulation of 30.0 +/- 2.1 ova (n = 5) at the next expected oestrus. Controls ovulated 12.0 +/- 0.8 ova (n = 6). Bovine LH, human LH, porcine LH, human chorionic gonadotrophin and pregnant mare serum gonadotrophin were effective in approximately doubling the number of ova spontaneously shed in the hamster. Ovine FSH (200 micrograms/pump) was most effective in increasing the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Osmotic minipumps (no. 2001, Alza Corp., Palo Alto, CA, U.S.A.) containing 400 µg ovine LH (S-24) in 0-01 mphosphate-buffered normal saline (PBS) with 0-1% bovine serum albumin (BSA), pH70, or PBS-BSA alone were inserted s.c. on Day 1 of the cycle at 09:00-10:00 h as previously described in detail by Garza et al (1984). Each hamster received a single pump.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic minipumps (no. 2001, Alza Corp., Palo Alto, CA, U.S.A.) containing 400 µg ovine LH (S-24) in 0-01 mphosphate-buffered normal saline (PBS) with 0-1% bovine serum albumin (BSA), pH70, or PBS-BSA alone were inserted s.c. on Day 1 of the cycle at 09:00-10:00 h as previously described in detail by Garza et al (1984). Each hamster received a single pump.…”
Section: Methodsmentioning
confidence: 99%
“…The study of Garza, Shaban & Terranova (1984) has shown that constant infusion of moderate amounts of LH during the cycle induced superovulation in the cyclic hamster. The superovulatory action of LH required the presence of the pituitary, suggesting that LH might synergize with FSH for spontaneous superovulation.…”
Section: Introductionmentioning
confidence: 99%
“…To insert the osmotic minipumps on Day 1 at 09:00-10:00 h, hamsters were anaesthetized lightly with ether and a 1-cm incision was made through the skin on the back between the scapulae as described in detail by Garza et al (1984) Gibco,Grand Island, NY, U.S.A.) supplemented with 01% bovine serum albumin. Three or 4 follicles/animal were stimulated in vitro in 1 ml incubation medium with 100 ng LH (NIH), or 0-1 or 1-0 µ -androstenedione.…”
Section: Methodsmentioning
confidence: 99%
“…Elevation of circulating concentrations of LH increases the number of ova shed by 2-3 times in the cyclic hamster (Garza, Shaban & Terranova, 1984); however, a few animals treated with human LH or hCG (in which numerous preovulatory follicles were observed) exhibited a blockade of ovulation. This blockade of ovulation was believed to be due to extremely elevated LH or hCG values which either altered the sensitivity of follicular gonadotrophin receptors to prevent ovulation or increased the serum concentration of progesterone resulting in a hypothalamic block to ovulation (Greenwald, 1978(Greenwald, , 1982.…”
Section: Introductionmentioning
confidence: 99%
“…In cyclic guinea pigs, both treatment of an antiserum to LH and infusion of ovine LH using an osmotic minipump induced superovulation [5,10] . However, these successful methods to cause increased ovulation can be used by only some specified investigaters.…”
Section: Superovulationmentioning
confidence: 99%